Impact of Heterogeneity on Opinion Dynamics: Heterogeneous Interaction Model - Xi Chen; Zhan Wu; Hongwei Wang; Wei Li (Complexity)
Considering the impact that physical distance and other properties have on the change of opinions, this paper introduces an intension model of the Hegselmann-Krause (KH) model—heterogeneous interaction (HI) model. Based on the classical KH model, HI model designs new interaction rules and the interactive radius considering the impact of heterogeneous attributes, such as physical distance, individual conformity, and authority. The experiment results show that the opinion evolution of the HI model will be similar to the classic KH model when the interactive radius is above the particular threshold value (σ>600). Unlike the KH model, which leads to the polarization phenomenon; most agents reach a consensus in HI model when the confidence radius equals 0.2, and the interactive radius remains within regulatory limits (150<σ<520). The conclusions show that interactive radius affects public opinion evolution. HI model can explain more conscious opinion evolution in real life and has significance that effectively guides public opinion.